2016
DOI: 10.1007/s11367-016-1080-2
|View full text |Cite
|
Sign up to set email alerts
|

LCA and LCC of the world’s longest pier: a case study on nickel-containing stainless steel rebar

Abstract: Purpose Built in 1941, the Progreso Pier was the first concrete structure in the world built with nickel-containing stainless steel reinforcement. The Pier has been in service for over 70 years without any significant repair or maintenance activities. The aim of this study was to understand the environmental and economic implications of selecting nickel-containing stainless steel reinforcement using the Progreso Pier as the case study. Methods A combined environmental life cycle assessment (LCA) and life cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 5 publications
3
12
0
4
Order By: Relevance
“…On the contrary, the worst environmental performances are those of the baseline design and the option based on stainless steel reinforcement. Such result confirms the relevant environmental burdens associated with the use of stainless steel in concrete reported by Mistry, Koffler, & Wong (2016). up to 17% greater than those of a properly chosen preventive strategy.…”
Section: Lcca Resultssupporting
confidence: 85%
“…On the contrary, the worst environmental performances are those of the baseline design and the option based on stainless steel reinforcement. Such result confirms the relevant environmental burdens associated with the use of stainless steel in concrete reported by Mistry, Koffler, & Wong (2016). up to 17% greater than those of a properly chosen preventive strategy.…”
Section: Lcca Resultssupporting
confidence: 85%
“…It is observed that an excessive concrete cover (R45 and R50) leads to great initial costs as well, due to the associated increase in the reinforcing steel demand. On the other hand, those solutions where the reinforcement material is modified, namely by using galvanized or stainless steel reinforcements, result in almost the highest initial costs, due to the high costs of materials [48]. At last, it is observed that the most expensive solutions in terms of initial costs are those where the reference concrete is modified with polymers.…”
Section: Resultsmentioning
confidence: 99%
“…The selected value is conservatively higher (67%) with respect to the value recommended by the White House Office of Management and Budget (OMB) in circular A-94 (revised November 2017) (White House Office of Management and Budget, 2017) for long-term federal investments (≥30 years). Typical commercial discount rate values for long-term investments range between 1% and 8% (Mistry et al, 2016). The present work considers a public works discount rate of 1%, based on a previous study Cadenazzi et al (2019a).…”
Section: Net Present Valuementioning
confidence: 99%